Solution of neutrosophic fractional differential equations by neutrosophic extension principal method - Rabih, Mohammed Nour A. (Edelweiss Applied Science and Technology, 2025)
This paper aims at a new approach for finding the solution of neutrosophic fuzzy fractional differential equations (NFFDEs) based on the Zadeh’s Extension Principle method. NFFDEs combine fractional-order systems with uncertainty, which deals with truth, indeterminacy, and falsity information. This approach competently addresses the challenges modeled by both the fractional derivatives and the indeterminate constructions characteristic of neutrosophic systems. The paper frames the theoretical framework, advances the solution process, and validates the usefulness of the method. Theoretical and numerical results validate that the Extension Principle method conserves vital properties of the fundamental systems while providing flexible and inclusive representations of uncertainty.